2018
DOI: 10.1242/jcs.214692
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules as platforms for probing liquid–liquid phase separation in cells – application to RNA-binding proteins

Abstract: Liquid–liquid phase separation enables compartmentalization of biomolecules in cells, notably RNA and associated proteins in the nucleus. Besides having critical functions in RNA processing, there is a major interest in deciphering the molecular mechanisms of compartmentalization orchestrated by RNA-binding proteins such as TDP-43 (also known as TARDBP) and FUS because of their link to neuron diseases. However, tools for probing compartmentalization in cells are lacking. Here, we developed a method to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…1d) but not when TDP-43, a RBP harboring a LCD but no PRM, was used as a negative control bait. In situ hybridization assays using a fluorescent poly(T) probes revealed that SAM68 directed onto microtubules has preserved its ability to bind to poly(A) mRNA (Supplementary Figure S4), which was also reported previously for TDP-43 [42]. As TDP-43 does not colocalize with ITSN1 on microtubules (Fig.…”
Section: Itsn1 Interacts With Sam68 In Cells and In Vitro Through Thesupporting
confidence: 84%
See 2 more Smart Citations
“…1d) but not when TDP-43, a RBP harboring a LCD but no PRM, was used as a negative control bait. In situ hybridization assays using a fluorescent poly(T) probes revealed that SAM68 directed onto microtubules has preserved its ability to bind to poly(A) mRNA (Supplementary Figure S4), which was also reported previously for TDP-43 [42]. As TDP-43 does not colocalize with ITSN1 on microtubules (Fig.…”
Section: Itsn1 Interacts With Sam68 In Cells and In Vitro Through Thesupporting
confidence: 84%
“…Previous analyses of the Intersectin interactome have revealed few RBPs as putative ITSN1 partners among which four of them harbored multiples PRMs, SAM68 [ 34 ], WBP11 [ 36 ], LARP6 and hnRNPK [ 35 ] (Table 1 ). As the presence of the PRM ligands may generate preferential interactions with SH3 domains, we decided to screen the relevance of the putative interactions of ITSN1 with SAM68, WBP11, LARP6 and hnRNPK in HeLa cells using a recently developed technology called « microtubule bench » [ 41 , 42 ]. The microtubule bench makes use, on the one hand, of a bait protein fused to the microtubule-binding domain of Tau (MBD) and a fluorescent label and, on the other hand, of a prey protein fused to a different fluorescent label that are expressed in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) concentrate in these structures, and have been demonstrated to strongly bind NSP5 50,60 , but not being sufficient to form viroplasm-like structures on their own, thus fulfilling the criteria of client proteins that partition into NSP5/NSP2 condensates. Lipid bilayers 61 , microtubules 62 and tubulin 63 can promote nucleation of biomolecular condensates and spatially regulate the kinetics of their formation in cells. Association of lipid droplets 64,65 and tubulin 15,49 with viroplasms is thus entirely consistent with our model of formation of viral replicative factories in RVinfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Flanking the CSD, this unstructured domain can bridge consecutive CSDs along the mRNA, as observed in the linear mRNA nucleoprotein filament formed by YB-1 in vitro 7 . Using microtubules as intracellular nanoplatforms to probe the co-localization between RNA-binding proteins 27 and their mixing 28 (microtubule bench assay), we showed that Lin28 and YB-1 co-localize in cells thanks to their common CSD, unlike the other tested RNA-binding proteins, G3BP1, FUS, TDP-43, LARP6 and HuR that do not have CSD (Supplementary Fig. S1b ).…”
Section: Introductionmentioning
confidence: 99%